Chemical and Rheological Characteristics of Orange-Yellow Cactus-Pear Pulp from Egypt - El-Samahy, S. K.; Abd El-Hady, E. A.; Habiba, R. A.; Moussa, T. E. (Journal of the Professional Association for Cactus Development, 2006)
Orange-yellow cactus-pear fruits from Egypt, called shameia variety, were collected at the same ripening stage from different regions to evaluate selected chemical properties and to study the rheological behavior of their pulps. The results obtained showed that there were differences between the pulp characteristics, which may be due to environmental effects. The fruits showed pulp ratios between 41.53% to 49.63%. All pulps had low acidity and high pH values ranging between 0.049% to 0.057% and 6.00 to 6.20, respectively. The rheological data obtained indicated that the flow behavior of all pulps was non-Newtonian besides exerting pseudoplastic behavior. Thixotropy values were 4.13 to 19.30 Pa s-1; yield stress reached 2.26 N m-2 at 20ºC.